2017
DOI: 10.1037/xhp0000422
|View full text |Cite
|
Sign up to set email alerts
|

Contingent capture is weakened in search for multiple features from different dimensions.

Abstract: Can observers maintain more than 1 attentional set and search for 2 features in parallel? Previous studies that relied on attentional capture by irrelevant distractors to answer this question focused on features from the same dimension and specifically, on color. They showed that 2 separate color templates can guide attention selectively and simultaneously. Here, the authors investigated attentional guidance by 2 features from different dimensions. In three spatial-cueing experiments, they compared contingent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 53 publications
7
29
0
Order By: Relevance
“…Previous studies on this topic have tested how IFP interacts with various forms of attention measured in a variety of ways, but they all involved top-down guidance or voluntary attention. For instance, some studies manipulated goal-driven rather than stimulus-driven attention to the singletons and did not have an independent manipulation of saliency (Belopolsky et al, 2010 ; Biderman, Biderman, Zivony, & Lamy, in press ; Folk & Remington, 2008 ; Irons et al, 2010 ). Other studies did make the singletons task irrelevant, but they neither manipulated nor measured spatial attention, merely inferring its effects or lack thereof (Fecteau, 2007 ; Huang et al, 2004 ; Kristjánsson, 2006 ; Michal et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on this topic have tested how IFP interacts with various forms of attention measured in a variety of ways, but they all involved top-down guidance or voluntary attention. For instance, some studies manipulated goal-driven rather than stimulus-driven attention to the singletons and did not have an independent manipulation of saliency (Belopolsky et al, 2010 ; Biderman, Biderman, Zivony, & Lamy, in press ; Folk & Remington, 2008 ; Irons et al, 2010 ). Other studies did make the singletons task irrelevant, but they neither manipulated nor measured spatial attention, merely inferring its effects or lack thereof (Fecteau, 2007 ; Huang et al, 2004 ; Kristjánsson, 2006 ; Michal et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…Searching for two or more target objects typically comes with performance costs relative to search for a single target, in terms of both speed and accuracy (Barrett & Zobay, 2014;Biderman, Biderman, Zivony, & Lamy, 2017;Houtkamp & Roelfsema, 2009;Menneer, Barrett, Phillips, Donnelly, & Cave, 2007;Stroud, Menneer, Cave, Donnelly, & Rayner, 2011). Performance suffers in particular when the search target changes from one trial to the next, resulting in what is known as a switch cost (Dombrowe, Donk, & Olivers, 2011;Found & Müller, 1996;Juola, Botella, & Palacios, 2004;Kristjánsson & Campana, 2010;Maljkovic & Nakayama, 1994;Monsell, 2003;Olivers & Humphreys, 2003;Olivers & Meeter, 2006;Wolfe, Butcher, Lee, & Hyle, 2003).…”
mentioning
confidence: 99%
“…Even though attentional control settings for multiple target colors can be maintained simultaneously, it has been suggested that search performance based on multiple attentional control settings is impaired (e.g., Biderman, Biderman, Zivony, & Lamy, 2017;Dombrowe, Donk, & Olivers, 2011;Meneer, Cave, & Donnelly, 2009). For example, in Dombrowe et al's experiment, in which participants were to search for two targets presented in a target display simultaneously, target search accuracy was lower when the two targets were defined by different colors than when they were defined by a single color.…”
Section: Discussionmentioning
confidence: 99%
“…For example, in Dombrowe et al's experiment, in which participants were to search for two targets presented in a target display simultaneously, target search accuracy was lower when the two targets were defined by different colors than when they were defined by a single color. This impairment is possibly due to the difficulty in maintaining multiple attentional control settings in working memory simultaneously (e.g., Biderman et al, 2017;Harris et al, 2015) or less computational efficiency when multiple attentional control settings are established than when a single attentional setting adopted (Harris et al, 2015). Thus, if the attentional control setting specifies values to ignore and other values to select when the target is defined with multiple colors and the distractor feature is certain, it is possible to maximize search performance with minimal effort.…”
Section: Discussionmentioning
confidence: 99%